Аленушкины сказки - Мамин-Сибиряк Дмитрий Наркисович (Библиотека школьника, 2018)
Экземпляры: 4 (20200926) / Инвентарный номер: 65111 / Цена: 120.80 / Сис.шифр: 84(2Роc=411.2) / Авт.знак: Т 51 / ГРНТИ: 17.82.93 / ББК: 84(2Роc=411.2)